ANALISIS KETERSEDIAAN DAN PENYEBARAN HASIL HUTAN BUKAN KAYU JENIS TANAMAN PEWARNA KAIN TENUN IKAT DI DAS RINDI, PADA POSISIDESA RINDI, KECAMATAN RINDI, KABUPATEN SUMBA TIMUR - Arianto Joh; Ludji Michael Riwu Kaho; Nixon Rammang (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2021)
A forest product not only focuses on the wood potential, but also focuses on the other such as wood output (FPNW). The use of woven fabric dyes is one of the Forest Products Not Wood that used by the Sumba community. This study aims to (1) Identify the availability and distribution of woven dyes in the customary forest area of the Rindi Watershed, especiallynin the Village of Rindi, Sub-District of Rindi, East Sumba District. (2) Know the varieties of plants used for natural dyes in Rindi Village, Rindi Sub-district, East Sumba District. It is conducted from Maret to May 2020 in Rindi Village, Rindi Sub-district, East Sumba District by using the vegetation analysis method, interview and literature studies. This Study shows that there are two successfully identified species of the Rubiceae family, namely Noni (Morinda citrifolia L.) and Indigo in the family of Fabaceae (Indigofera tinctoria L.). The important value index of Mengkudu (Morinda citrifolia L.) is 203.96 amount and high classified in this land, while the IndigoferaTinctoria L. is found 27.5 amount as the medium one. The spread of woven fabrics' dyes on many wild plants has resulted unevenly spreading, where it is found around forests, farmland and thickets. The root of Noni will produce the color of red, while the blue color is produced by the leaves of Indigo plant.